1990
DOI: 10.1126/science.2396096
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic Depth Discrimination in the Visual Cortex: Neurons Ideally Suited as Disparity Detectors

Abstract: The possibility has been explored that a subset of physiologically identifiable cells in the visual cortex is especially suited for the processing of stereoscopic depth information. First, characteristics of a disparity detector that would be useful for such processing were outlined. Then, a method was devised by which detailed binocular response data were obtained from cortical cells. In addition, a model of the disparity detector was developed that includes a plausible hierarchical arrangement of cortical ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

30
669
3
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 672 publications
(703 citation statements)
references
References 23 publications
30
669
3
1
Order By: Relevance
“…Such emergent boundary and surface representations, rather than just the energy impinging on our retinas, define the form percepts of which we are consciously aware. Precise orientationally tuned comparisons of left eye and right eye inputs are used to compute sharp estimates of the relative depth of an object from its observer 25,26 , and thereby to form three-dimensional boundary and surface representations of objects separated from their backgrounds 7 .…”
Section: Complementary Form and Motion Interactionsmentioning
confidence: 99%
“…Such emergent boundary and surface representations, rather than just the energy impinging on our retinas, define the form percepts of which we are consciously aware. Precise orientationally tuned comparisons of left eye and right eye inputs are used to compute sharp estimates of the relative depth of an object from its observer 25,26 , and thereby to form three-dimensional boundary and surface representations of objects separated from their backgrounds 7 .…”
Section: Complementary Form and Motion Interactionsmentioning
confidence: 99%
“…They classified cells into a few discrete categories, although it now appears that Center for Neurobiology and Behavior Columbia University these categories represent idealized cases from a continuous distribution (LeVay and Voigt, 1988). More reNew York, New York 10032 cently, Ohzawa et al (1990Ohzawa et al ( , 1996 provided detailed quantitative mapping of binocular receptive fields of the We perceive the world in three-dimensions even though cat visual cortical cells and suggested models for simuthe input to our visual system, the images projected lating their responses. While these and many other exonto our two retinas, has only two spatial dimensions.…”
mentioning
confidence: 99%
“…These curves alone are not very useful from a computational point of view because a response can be read from a disparity tuning curve only when the stimulus disparity is already known. We need a quantitative procedure for computing an unknown disparity in a pair of retinal images from the responses of complex cells to the images.Fortunately, a method for determining the responses of binocular complex cells has recently been proposed by Ohzawa et al (1990) based on their quantitative physiological studies (see also Ferster, 1981). These investigators found that a binocular complex cell in the cat primary visual cortex can be simulated by summing up the squared responses of a quadrature pair of simple cells, and the simple cell responses, in turn, can be simulated by adding the visual inputs on their left and right receptive fields (see Figure 5).…”
mentioning
confidence: 99%
See 2 more Smart Citations